APLIKASI SISTEM PAKAR DIAGNOSIS KERUSAKAN DAN SIMULASI PERAKITAN KOMPUTER BERBASIS WEB MENGGUNAKAN METODE FORWARD CHAINING - Agie Nugraha Pratama; Rysa Sahrial (POLITEKNIK LP3I JAKARTA, 2024)
A computer is a set of objects that we can find in various places, especially in offices or homes as a tool to help complete various tasks. In Greek, a computer is called